THE EFFECT OF JOB SATISFACTION, CAREER DEVELOPMENT AND COMMITMENT TO TURNOVER INTENTION IN CAKRAWALA MITRA BERSAMA - Nining Yuningsih (Journal of Research in Business, Economics, and Education, 2020)
Job performance will improve if the company can meet the needs and job satisfaction of its employees and is supported by companies that enhance the career development of their employees. employees assume the performance done in the company as he expected and the company has a good future for these employees, this can increase the organizational commitment of employees in the company, so that company goal will be achieved. The problem in this study is whether the lack of job satisfaction affects the high level of turnover intention, whether the lack of career development affects the high level of turnover intention and whether the organizational commitment of employees influences the level of turnover intention in PT Cakrawala Mitra Bersama. This research was conducted by simple random sampling and carried out on the employees of PT. Cakrawala Mitra Bersama. Based on hypothesis testing using the t-test (partial) that the Satisfaction variable influences Turnover Intention, while the Career Development variable has no effect on Turnover Intention and the Organizational Commitment variable does not affect the decline of Turnover Intention.